Total smoking bans in psychiatric inpatient services: a survey of perceived benefits, barriers and support among staff - Knight Jenny; Baker Amanda; Wiggers John; Bowman Jenny; Wye Paula; Carr Vaughan; Terry Margarett; Clancy Richard (BMC, 2010)
Abstract Background The introduction of total smoking bans represents an important step in addressing the smoking and physical health of people with mental illness. Despite evidence indicating the importance of staff support in the successful implementation of smoking bans, limited research has examined levels of staff support prior to the implementation of a ban in psychiatric settings, or factors that are associated with such support. This study aimed to examine the views of psychiatric inpatient hospital staff regarding the perceived benefits of and barriers to implementation of a successful total smoking ban in mental health services. Secondly, to examine the level of support among clinical and non-clinical staff for a total smoking ban. Thirdly, to examine the association between the benefits and barriers perceived by clinicians and their support for a total smoking ban in their unit. Methods Cross-sectional survey of both clinical and non-clinical staff in a large inpatient psychiatric hospital immediately prior to the implementation of a total smoking ban. Results Of the 300 staff, 183 (61%) responded. Seventy-three (41%) of total respondents were clinical staff, and 110 (92%) were non-clinical staff. More than two-thirds of staff agreed that a smoking ban would improve their work environment and conditions, help staff to stop smoking and improve patients' physical health. The most prevalent clinician perceived barriers to a successful total smoking ban related to fear of patient aggression (89%) and patient non-compliance (72%). Two thirds (67%) of all staff indicated support for a total smoking ban in mental health facilities generally, and a majority (54%) of clinical staff expressed support for a ban within their unit. Clinical staff who believed a smoking ban would help patients to stop smoking were more likely to support a smoking ban in their unit. Conclusions There is a clear need to more effectively communicate to staff the evidence that consistently applied smoking bans do not increase patient aggression. There is also a need to communicate the benefits of smoking bans in aiding the delivery of smoking cessation care, and the benefits of both smoking bans and such care in aiding patients to stop smoking.